Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Sure! Let's dive into the problem step-by-step:
### Part (a): Finding the Domain of Each Function and Combinations
1. Domain of [tex]\( f(x) = x - 2 \)[/tex]:
- The function [tex]\( f(x) = x - 2 \)[/tex] is a linear function.
- Linear functions are defined for all real numbers.
- Hence, domain of [tex]\( f \)[/tex] is [tex]\(\mathbb{R}\)[/tex] (all real numbers).
2. Domain of [tex]\( g(x) = \sqrt{x + 1} \)[/tex]:
- The function [tex]\( g(x) = \sqrt{x + 1} \)[/tex] is defined for the values inside the square root being non-negative.
- So, [tex]\( x + 1 \geq 0 \implies x \geq -1 \)[/tex].
- Hence, domain of [tex]\( g \)[/tex] is [tex]\([-1, \infty)\)[/tex].
3. Domain of [tex]\( f+g \)[/tex]:
- [tex]\( (f+g)(x) = f(x) + g(x) = (x - 2) + \sqrt{x + 1} \)[/tex].
- The domain is the intersection of the domains of [tex]\( f \)[/tex] and [tex]\( g \)[/tex].
- Intersection of [tex]\(\mathbb{R}\)[/tex] and [tex]\([-1, \infty)\)[/tex] is [tex]\([-1, \infty)\)[/tex].
- Hence, domain of [tex]\( f+g \)[/tex] is [tex]\([-1, \infty)\)[/tex].
4. Domain of [tex]\( f-g \)[/tex]:
- [tex]\( (f-g)(x) = f(x) - g(x) = (x - 2) - \sqrt{x + 1} \)[/tex].
- Domain is the same as for [tex]\( f+g \)[/tex] (intersection of [tex]\(\mathbb{R}\)[/tex] and [tex]\([-1, \infty)\)[/tex]).
- Hence, domain of [tex]\( f-g \)[/tex] is [tex]\([-1, \infty)\)[/tex].
5. Domain of [tex]\( f \cdot g \)[/tex]:
- [tex]\( (fg)(x) = f(x) \cdot g(x) = (x - 2) \cdot \sqrt{x + 1} \)[/tex].
- Domain is the same as for [tex]\( f+g \)[/tex] (intersection of [tex]\(\mathbb{R}\)[/tex] and [tex]\([-1, \infty)\)[/tex]).
- Hence, domain of [tex]\( f \cdot g \)[/tex] is [tex]\([-1, \infty)\)[/tex].
6. Domain of [tex]\( \frac{f}{g} \)[/tex]:
- [tex]\( \left(\frac{f}{g}\right)(x) = \frac{f(x)}{g(x)} = \frac{x - 2}{\sqrt{x + 1}} \)[/tex].
- [tex]\( g(x) \neq 0 \)[/tex], so [tex]\( \sqrt{x + 1} \neq 0 \implies x \neq -1 \)[/tex].
- Intersection of [tex]\(\mathbb{R}\)[/tex] and [tex]\([-1, \infty)\)[/tex] excluding [tex]\( x = -1 \)[/tex].
- Hence, domain of [tex]\( \frac{f}{g} \)[/tex] is [tex]\((-1, \infty)\)[/tex].
7. Domain of [tex]\( \frac{g}{f} \)[/tex]:
- [tex]\( \left(\frac{g}{f}\right)(x) = \frac{g(x)}{f(x)} = \frac{\sqrt{x + 1}}{x - 2} \)[/tex].
- [tex]\( f(x) \neq 0 \)[/tex], so [tex]\( x - 2 \neq 0 \implies x \neq 2 \)[/tex].
- Intersection of [tex]\(\mathbb{R}\)[/tex] and [tex]\([-1, \infty)\)[/tex] excluding [tex]\( x = 2 \)[/tex].
- Hence, domain of [tex]\( \frac{g}{f} \)[/tex] is [tex]\(\left[-1, 2\right) \cup \left(2, \infty\right)\)[/tex].
### Part (b): Calculating the Expressions
1. [tex]\( (f+g)(x) \)[/tex]:
[tex]\[ (f+g)(x) = f(x) + g(x) = (x - 2) + \sqrt{x + 1} = x + \sqrt{x + 1} - 2 \][/tex]
2. [tex]\( (f-g)(x) \)[/tex]:
[tex]\[ (f-g)(x) = f(x) - g(x) = (x - 2) - \sqrt{x + 1} = x - \sqrt{x + 1} - 2 \][/tex]
3. [tex]\( (fg)(x) \)[/tex]:
[tex]\[ (fg)(x) = f(x) \cdot g(x) = (x - 2) \cdot \sqrt{x + 1} \][/tex]
4. [tex]\( (ff)(x) \)[/tex]:
[tex]\[ (ff)(x) = f(f(x)) = f(x - 2) = (x - 2) - 2 = x - 4 \][/tex]
5. [tex]\( \left(\frac{f}{g}\right)(x) \)[/tex]:
[tex]\[ \left(\frac{f}{g}\right)(x) = \frac{f(x)}{g(x)} = \frac{x - 2}{\sqrt{x + 1}} \][/tex]
6. [tex]\( \left(\frac{g}{f}\right)(x) \)[/tex]:
[tex]\[ \left(\frac{g}{f}\right)(x) = \frac{g(x)}{f(x)} = \frac{\sqrt{x + 1}}{x - 2} \][/tex]
This concludes the detailed step-by-step solution for the given functions and their combinations along with their domains.
### Part (a): Finding the Domain of Each Function and Combinations
1. Domain of [tex]\( f(x) = x - 2 \)[/tex]:
- The function [tex]\( f(x) = x - 2 \)[/tex] is a linear function.
- Linear functions are defined for all real numbers.
- Hence, domain of [tex]\( f \)[/tex] is [tex]\(\mathbb{R}\)[/tex] (all real numbers).
2. Domain of [tex]\( g(x) = \sqrt{x + 1} \)[/tex]:
- The function [tex]\( g(x) = \sqrt{x + 1} \)[/tex] is defined for the values inside the square root being non-negative.
- So, [tex]\( x + 1 \geq 0 \implies x \geq -1 \)[/tex].
- Hence, domain of [tex]\( g \)[/tex] is [tex]\([-1, \infty)\)[/tex].
3. Domain of [tex]\( f+g \)[/tex]:
- [tex]\( (f+g)(x) = f(x) + g(x) = (x - 2) + \sqrt{x + 1} \)[/tex].
- The domain is the intersection of the domains of [tex]\( f \)[/tex] and [tex]\( g \)[/tex].
- Intersection of [tex]\(\mathbb{R}\)[/tex] and [tex]\([-1, \infty)\)[/tex] is [tex]\([-1, \infty)\)[/tex].
- Hence, domain of [tex]\( f+g \)[/tex] is [tex]\([-1, \infty)\)[/tex].
4. Domain of [tex]\( f-g \)[/tex]:
- [tex]\( (f-g)(x) = f(x) - g(x) = (x - 2) - \sqrt{x + 1} \)[/tex].
- Domain is the same as for [tex]\( f+g \)[/tex] (intersection of [tex]\(\mathbb{R}\)[/tex] and [tex]\([-1, \infty)\)[/tex]).
- Hence, domain of [tex]\( f-g \)[/tex] is [tex]\([-1, \infty)\)[/tex].
5. Domain of [tex]\( f \cdot g \)[/tex]:
- [tex]\( (fg)(x) = f(x) \cdot g(x) = (x - 2) \cdot \sqrt{x + 1} \)[/tex].
- Domain is the same as for [tex]\( f+g \)[/tex] (intersection of [tex]\(\mathbb{R}\)[/tex] and [tex]\([-1, \infty)\)[/tex]).
- Hence, domain of [tex]\( f \cdot g \)[/tex] is [tex]\([-1, \infty)\)[/tex].
6. Domain of [tex]\( \frac{f}{g} \)[/tex]:
- [tex]\( \left(\frac{f}{g}\right)(x) = \frac{f(x)}{g(x)} = \frac{x - 2}{\sqrt{x + 1}} \)[/tex].
- [tex]\( g(x) \neq 0 \)[/tex], so [tex]\( \sqrt{x + 1} \neq 0 \implies x \neq -1 \)[/tex].
- Intersection of [tex]\(\mathbb{R}\)[/tex] and [tex]\([-1, \infty)\)[/tex] excluding [tex]\( x = -1 \)[/tex].
- Hence, domain of [tex]\( \frac{f}{g} \)[/tex] is [tex]\((-1, \infty)\)[/tex].
7. Domain of [tex]\( \frac{g}{f} \)[/tex]:
- [tex]\( \left(\frac{g}{f}\right)(x) = \frac{g(x)}{f(x)} = \frac{\sqrt{x + 1}}{x - 2} \)[/tex].
- [tex]\( f(x) \neq 0 \)[/tex], so [tex]\( x - 2 \neq 0 \implies x \neq 2 \)[/tex].
- Intersection of [tex]\(\mathbb{R}\)[/tex] and [tex]\([-1, \infty)\)[/tex] excluding [tex]\( x = 2 \)[/tex].
- Hence, domain of [tex]\( \frac{g}{f} \)[/tex] is [tex]\(\left[-1, 2\right) \cup \left(2, \infty\right)\)[/tex].
### Part (b): Calculating the Expressions
1. [tex]\( (f+g)(x) \)[/tex]:
[tex]\[ (f+g)(x) = f(x) + g(x) = (x - 2) + \sqrt{x + 1} = x + \sqrt{x + 1} - 2 \][/tex]
2. [tex]\( (f-g)(x) \)[/tex]:
[tex]\[ (f-g)(x) = f(x) - g(x) = (x - 2) - \sqrt{x + 1} = x - \sqrt{x + 1} - 2 \][/tex]
3. [tex]\( (fg)(x) \)[/tex]:
[tex]\[ (fg)(x) = f(x) \cdot g(x) = (x - 2) \cdot \sqrt{x + 1} \][/tex]
4. [tex]\( (ff)(x) \)[/tex]:
[tex]\[ (ff)(x) = f(f(x)) = f(x - 2) = (x - 2) - 2 = x - 4 \][/tex]
5. [tex]\( \left(\frac{f}{g}\right)(x) \)[/tex]:
[tex]\[ \left(\frac{f}{g}\right)(x) = \frac{f(x)}{g(x)} = \frac{x - 2}{\sqrt{x + 1}} \][/tex]
6. [tex]\( \left(\frac{g}{f}\right)(x) \)[/tex]:
[tex]\[ \left(\frac{g}{f}\right)(x) = \frac{g(x)}{f(x)} = \frac{\sqrt{x + 1}}{x - 2} \][/tex]
This concludes the detailed step-by-step solution for the given functions and their combinations along with their domains.
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.